2014
DOI: 10.1371/journal.pone.0094818
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Alpha-Toxin Mediates General and Cell Type-Specific Changes in Metabolite Concentrations of Immortalized Human Airway Epithelial Cells

Abstract: Staphylococcus aureus alpha-toxin (Hla) is a potent pore-forming cytotoxin that plays an important role in the pathogenesis of S. aureus infections, including pneumonia. The impact of Hla on the dynamics of the metabolome in eukaryotic host cells has not been investigated comprehensively. Using 1H-NMR, GC-MS and HPLC-MS, we quantified the concentrations of 51 intracellular metabolites and assessed alterations in the amount of 25 extracellular metabolites in the two human bronchial epithelial cell lines S9 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 45 publications
3
35
0
Order By: Relevance
“…6C). This clearly indicated that the Ca 2ϩ pumps refilling the intracellular stores were still functional at 1 or 2 h of rHla treatment of cells despite the substantial loss of ATP that had been observed during this time period in rHla-treated cells (17). This result corresponds with previous findings (52) that a cytosolic ATP concentration of 0.1 mmol/l (i.e., only 1/10 of the original concentration) is sufficient to maintain the intracellular calcium stores of cells in a completely filled state.…”
Section: L680 S Aureus ␣-Toxin and Host Cell Ion Permeabilitymentioning
confidence: 89%
See 2 more Smart Citations
“…6C). This clearly indicated that the Ca 2ϩ pumps refilling the intracellular stores were still functional at 1 or 2 h of rHla treatment of cells despite the substantial loss of ATP that had been observed during this time period in rHla-treated cells (17). This result corresponds with previous findings (52) that a cytosolic ATP concentration of 0.1 mmol/l (i.e., only 1/10 of the original concentration) is sufficient to maintain the intracellular calcium stores of cells in a completely filled state.…”
Section: L680 S Aureus ␣-Toxin and Host Cell Ion Permeabilitymentioning
confidence: 89%
“…Another mechanism potentially explaining the increase in cytosolic calcium in rHla-exposed cells would be that the rHla-induced rapid release of substantial amounts of ATP from the cytosol to the extracellular space, which has been observed in different cell types upon treatment with ␣-toxin (17,27,36), may result in very low cytosolic ATP concentrations. The lack of cellular ATP, in turn, may compromise the activity of Ca 2ϩ -ATPases in the membranes of endoplasmic calcium stores (SERCA) or in the plasma membrane (PMCA) (48).…”
Section: L680 S Aureus ␣-Toxin and Host Cell Ion Permeabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…For this control the pH was set to 6.9, corresponding to the pH of a bacterial culture at OD 600 0.4. Samples of cellular extracts were generated and extracted as described previously (Gierok et al, 2014). In brief, the supernatant was collected separately.…”
Section: Methodsmentioning
confidence: 99%
“…Intracellular metabolites were extracted from cells with methanol/water/chloroform in a ratio of 5:5:1. After addition of internal standards, metabolites were lyophilized and identified and quantified by GC/MS and LC/MS as described before [38].…”
Section: Metabolome Analysis Of A549 Cellsmentioning
confidence: 99%